2014
DOI: 10.1103/physreve.89.032102
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of molecular chains with asymmetric potentials of pair interactions

Abstract: We provide molecular-dynamics simulation of heat transport in one-dimensional molecular chains with different interparticle pair potentials. We show that the thermal conductivity is finite in the thermodynamic limit in chains with the potentials that allow for bond dissociation. The Lennard-Jones, Morse, and Coulomb potentials are such potentials. The convergence of the thermal conductivity is provided by phonon scattering on the locally strongly stretched loose interatomic bonds at low temperature and by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
70
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 33 publications
12
70
0
Order By: Relevance
“…Das, Dhar, and Narayan [34]; Wang, Hu, and Li [35], and Savin and Kosevich [36] repeated the same kind of simulations and concluded that finite heat conductivity is actually a finite-size effect and does not correspond to the expected universal scaling behavior that should be attained in the thermodynamic limit. In practice, the seemingly normal diffusion observed in certain dynamical regimes of nonlinear lattices with asymmetric interaction should crossover to the power-law scaling γ = 1/3 for sufficiently large sizes and sufficiently long times.…”
Section: Introductionmentioning
confidence: 93%
“…Das, Dhar, and Narayan [34]; Wang, Hu, and Li [35], and Savin and Kosevich [36] repeated the same kind of simulations and concluded that finite heat conductivity is actually a finite-size effect and does not correspond to the expected universal scaling behavior that should be attained in the thermodynamic limit. In practice, the seemingly normal diffusion observed in certain dynamical regimes of nonlinear lattices with asymmetric interaction should crossover to the power-law scaling γ = 1/3 for sufficiently large sizes and sufficiently long times.…”
Section: Introductionmentioning
confidence: 93%
“…Coming back to 1D model chains, up to now, many ingredients related to anomalous thermal conduction have been carefully considered, among them are chaos [28][29][30][31][32][33], conservation of momentum [34][35][36][37], asymmetric interactions [38][39][40][41][42], linearity [33,[43][44][45][46], integrability [47], pressure [48,49], surface scattering effect [50] etc. Particularly, the viewpoint that a system with (without) a momentum conservation property should disobey (obey) Fourier's law has been widely accepted, although there are still some contradictory results on this issue [51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Subsequent studies [3][4][5][6][7] show that this remains an controversial issues. Conflicts among the studies may partly come from the un-unified setting of parameter regimes of the asymmetric anharmonic terms, which is less focused previously.…”
Section: Introductionmentioning
confidence: 99%